An Acoustic Analysis of Stop Consonants in Gojri Language - Khalid, Nabeela; Khan, Abdul Qadir (Pakistan Languages and Humanities Review, 2025)
The purpose of the study is to identify the stop consonants of Gojri language and measure their acoustic properties. Gojri is an Indo- Aryan language, which is spoken by Gujjar community in Azad Jammu and Kashmir. The study is descriptive in nature and used mixed method approach. Data were collected from twenty native speakers of the language. Identified stops are recorded in VCV context for acoustic analysis. The results show that Gojri language contains twelve stop consonant sounds. These sounds are produced from diverse places of articulation; bilabial, dental, retroflex and velar. Voicing contrast shows three way voicing with no voiced aspirated segment. Acoustic analysis reveals that VOT, closure duration and burst and major acoustic cues which vary in terms of place of articulation and voicing. It is the first acoustic analysis of Gojri stop consonants and further researches can be conducted on segmental and supragemental features of the language.